Phytochemical Analysis of Ampelopteris Prolifera (Retzius) Copeland - Poudel, Madhav; Rajbhandari, Meena (Nepal Journal of Science and Technology, 2020)
The fronds of Ampelopteris prolifera are used in stomach ache as well as vegetable. Dried and powdered fronds of A. prolifera was extracted successively with hexane, chloroform, ethyl acetate, methanol and 50% aqueous methanol. The results of phytochemical screening revealed that alkaloids were absent in all extracts. Hexane extract showed the absence of all the tested phytochemicals while chloroform extract showed the presence of only terpenoids and quinones. Ethylacetate extract showed the presence of all tested phytochemicals except quinones and saponins. Methanol and 50% aqueous methanol extracts showed the presence of phenolics, flavonoids, terpenoids, glycosides, tannins, quinones and saponins. The total content of phenolics, flavonoids, tannins and sugars as well as antioxidant activity were determined in ethyl acetate, methanol and 50% aqueous methanol extracts. Total phenolic content was measured spectrophotometrically by using Folin-Ciocalteu, total flavonoid content by using aluminium chloride, total hydrolyzable tannin content by using Folin-Ciocalteu, total condensed tannin content using vanillin-HCl and total sugar content by using anthrone reagent. Gallic acid was used as the standard for the calibration of phenolics, catechin for flavonoids and condensed tannins, tannic acid for hydrolyzable tannins and glucose for carbohydrates. The highest amount of phenolic was detected in 50% methanol extract (114.27±10.37 mg GAE/g). The highest amount of flavonoid was detected in ethylacetate extract (151.47±3.57 mg CE/g extract). The highest amount of hydrolyzable tannin was detected in 50% methanol extract (31.21±2.14 mg TAE/g extract). The highest amount of condensed tannin was detected in ethylacetate extract (337.50±5.00 mg CE/g extract), and the highest amount of sugar was detected in methanol extract (809.74±7.86 mg GE/g). The antioxidant activity was determined by using DPPH free radical and IC50 value was determined. All the tested extracts showed only weak antioxidant activity. Among the tested extracts, 50% aqueous methanol extract showed better activity with an IC50 value of 185.03 μg/mL. The HPLC-ESI-MS analysis of methanol extract allowed the tentative identification of peganine, 1-methyltryptophan and rutin. The study thus demonstrates the potential value of A. proliferain the medicinal application.